Tailoring the Structural and Optical Properties of Oxychloride Magnesium Tellurite Glass with the Addition of Samarium Ions - Nurul Ainaa Najihah, Busra; Harizah, Nadzmi; Rodziah, Nazlan (Penerbit UNIMAP, 2023)
In this study, samarium-doped oxychloride magnesium tellurite glass with composition (79−x)TeO2−xMgO−20Li2O−1Sm2O3 (Series 1) and (79−x)TeO2xMgCl2−20Li2O−1Sm2O3 (Series 2) with 0 ≤ x ≤ 15 mol% was prepared by the melt-quenching technique. The structural and optical properties of synthesized samples were investigated, and the XRD results dictated an amorphous nature for both samples. The glass density of both Series 1 and 2 decreased with increasing MgO and MgCl2 content. However, the molar volume behaves in a completely opposite manner to an increase in MgO or MgCl2 content. FTIR spectra revealed from the vibrational wavenumber shift of TeO4 and TeO3 structural units showed a significant rise in HOH vibration mode, which implies its usefulness in boosting water and light absorption. Four absorbance bands were observed via UV-Vis NIR, while the indirect optical band gap around (3.42–3.36) eV and (3.42−3.30) eV for Series 1 and Series 2 were observed from UV-Vis spectroscopy. The emission spectra from the photoluminescence study revealed four distinct bands centered at 562.54, 599.14, 645.63 and 708.40 nm which are attributed to the transition from 4G5/2 – 6HJ/2 (J = 5,7,9,11) of states of Sm3+. The optimum glass with a composition of TeO-MgO 15% demonstrates a high potential for optical device development.